Hikayat Prang Sabi: The Narrative of History and Religion as a Tool for Mobilizing Social Movements in Aceh - Y Yusmadi; M Isa; Dedy Haryadi Hasan; Darmadi Darmadi (Electronic Journal of Education, Social Economics and Technology, 2025)
The Hikayat Prang Sabi (Acehnese Saga) is a literary work known to contain historical and religious narratives that are full of the struggles of the Acehnese people. This study aims to reveal more about the Hikayat Prang Sabi, especially the historical and religious narratives as a means of mobilization in the social movements that occurred in Aceh. The research method uses literature studies from previous journals as qualitative research. The findings show that the Hikayat Prang Sabi contains themes such as struggle and resistance against the colonizers, and also contains religious values such as jihad, love of the homeland, piety and tawakal. The historical and religious narratives contained in this story are known to be able to inspire the Acehnese people to move in order to raise the spirit of carrying out social movements. Several social movements that are rooted in the struggle of the Acehnese people against the colonizers or the struggle to defend the truth of Islam are the Aceh War, or the Free Aceh Movement (GAM). From this social movement, it is known to have had an impact on various aspects of life in Aceh such as social, political, and cultural aspects.